(untitled) (Marketing Journal, 2025)
This article analyzes the experience of advanced foreign countries in shaping an innovative economy through a systematic literature review (SLR). Employing a method based on the PRISMA guidelines, several scientific sources published in recent years from t he Scopus, Web of Science, and ResearchGate databases were subjected to thematic analysis. The results indicate that in countries such as the USA, the European Union, Japan, and South Korea, multinational corporations, global value chains, and innovations in developing economies have been successfully advanced. Taking into account trends such as artificial intelligence, digital transformation, and sustainable development, recommendations for transitional economies include increasing R&D expenditures, incent ivizing private sector investments, and strengthening global cooperation. The study emphasizes the necessity of adapting innovation policies in developing countries to advanced practices.